An analysis of 100 referrals for depression from primary care to an adult mental health service. (18th September 2013) - Rogers, C.; Heatherington, S.; Carroll, M.; Leonard, M.; Cullen, W.; Meagher, D.
Abstract : Objectives: Improving the interface between primary care and mental health services is a key target in current healthcare policy in Ireland. This study examines the content of referrals from primary care to a community mental health service for apparent depression. Method: We retrospectively reviewed the clinical records of 100 patients with depression who consecutively attended a specialist mental health service in Ireland's midwest region. Records were reviewed for demographic and clinical information provided by the doctor at the time of referral, subsequent service engagement, diagnosis and treatment initiated. Results: There was considerable variation in the content and presentation of information contained in referral letters. Eleven per cent used structured HSE mental health referral forms. Seventy-six per cent of referrals contained clear information regarding name, address, symptoms and treatment previously initiated. Specifically, low mood, biological symptoms of depression and illness severity were documented in 43%, 34% and 27%, respectively. Suicide risk was documented in 20%. More detail was significantly associated with more severe illness. At initial specialist assessment, 71% had commenced antidepressant treatment, with 11% having received an adequate trial of a first antidepressant and 3% an adequate trial of two antidepressants. Two-thirds were diagnosed with mild/moderate depression. Initiation of antidepressant treatment was linked to subsequent diagnosis of depressive illness by mental health services ( p < 0.001). Conclusions: Our findings indicate variable referral practices from general practice to mental health in our region. Most referrals were for mild to moderate depression. Poor access to psychological services locally may be a key factor in this phenomenon.